2017
DOI: 10.3389/fmicb.2017.01308
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Substitution K470R in the Nucleoprotein Increases the Virulence of H5N1 Influenza A Virus in Mammals

Abstract: H5N1 is a highly pathogenic influenza A virus (IAV) and poses a major threat to the public health. The nucleoprotein (NP) has a multiple functions during the viral life cycle, however, the precise role of NP mutants in viral replication and pathogenicity is not completely understood. Here, we attempted to identify five residues in NP that may contribute to viral replication or pathogenicity. Of these, K227R, K229R, and K470R viruses were successfully rescued by reverse genetic, but the K91R and K198R viruses w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Several publications have reported that modifying NP residues can affect the intracell localization of proteins and the later formation of the virion (Ince, Gueye‐Mbaye, Bennink, & Yewdell, ; Ninpan et al, ; Shu, Bean, & Webster, ), which correlates with decreased activity of RNPs formed with mutant NP observed in this study. An example of this was the study of Chen et al (), who found that the modifications of residues 91 and 198 in the influenza A virus NP altered normal NP localization, decreasing RNP activity.…”
Section: Discussionmentioning
confidence: 99%
“…Several publications have reported that modifying NP residues can affect the intracell localization of proteins and the later formation of the virion (Ince, Gueye‐Mbaye, Bennink, & Yewdell, ; Ninpan et al, ; Shu, Bean, & Webster, ), which correlates with decreased activity of RNPs formed with mutant NP observed in this study. An example of this was the study of Chen et al (), who found that the modifications of residues 91 and 198 in the influenza A virus NP altered normal NP localization, decreasing RNP activity.…”
Section: Discussionmentioning
confidence: 99%
“…Besides K103, we found five other lysines 91, 198, 227, 229, and 470 of NP could either be modified by acetylation using mass spectrometry. In our previous study, we investigated their functions in influenza virus life cycle ( 36 ). Of these, the K91R and K198R showed decreased the polymerase activity, and K91R and K198R mutants cannot yield recombinant viruses, while K227R viruses showed a similar virulence as rWT.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the replication efficiencies of K229R mutant viruses were attenuated in vivo and in vitro . Importantly, rK470R increased the virus’s virulence in both cell culture and animal model ( 36 ). We have also substituted all lysine (K) residues with arginine(R).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The amino acid mutations S224P, N383D, and I353R in PA increased the virulence of H5N1 influenza virus in mice and ducks (16)(17)(18). The amino acid mutations M105V, I109T, and A184K in NP increased the virulence of H5N1 virus in chickens (19)(20)(21), whereas the K470R mutation in NP increased the virulence of H5N1 virus in mice (22). Two amino acid mutations in M1, N30D and T215A, synergistically increased the virulence of H5N1 virus in mice (23).…”
mentioning
confidence: 99%